A quest for the atgeir: the unknown Viking weapon in Icelandic sagas and archaeological data - Shtyryakova Yulia (Acta Periodica Duellatorum)
Today we know much about the culture of the Viking Age, but there are still gaps to fill. One of them is what the legendary weapon called atgeirr in Icelandic sagas really was. Nowadays researchers prefer to view atgeir as a kind of spear. But the defining features of atgeir are not clearly described and the range of different kinds of spearheads suggested as related to this weapon is frustratingly wide.